Advances in sampling theory and techniques - I︠A︡roslavskiĭ, L. P. (SPIE Press monograph ;, 2020)
"This book presents the current state of the art of digital engineering, as well as recent proposals for optimal methods of signal and image non-redundant sampling and interpolation-error-free resampling. Topics include classical sampling theory, conventional sampling, the peculiarities of sampling 2D signals, artifacts, compressed sensing, fast algorithms, the discrete uncertainty principle, and sharply-band-limited discrete signals and basis functions with sharply limited support. Exercises based in MATLAB supplement the text throughout"--